The dark tetrad of personality and the accounting information quality: the moderating effect of corporate reputation - Góis, Alan Diógenes (2017)
The Upper Echelons Theory states that CEO characteristics, among them the Dark Tetrad (narcissism, Machiavellianism, psychopathy, and sadism) of personality, affect decision-making. In an accounting context, the presence of the Dark Tetrad of personality in CEOs can reduce accounting information quality because the personalities of the Dark Tetrad are associated with callousness, impulsivity, manipulation, criminality, grandiosity, enjoyment of cruelty, and misconduct, therefore CEOs with these traits are likely to manipulate earnings or commit fraud. However, companies with strong reputation due to the credibility and trustworthiness built into the company values and culture can reduce the effect of dark personality in accounting information quality. In such context, this study aims to investigate the moderating effect of corporate reputation on the relationship between the Dark Tetrad of personality and accounting information quality. The main assumption is that CEOs with strong Dark Tetrad traits engage more in earnings management and fraud; however, in companies with strong reputation, earnings management and fraud would be lower due to the values, structures, and formal or informal rules built around corporate reputation. This implies that companies with strong reputation tend to suppress the opportunistic actions of CEOs, enabling better accounting information quality. The research design was divided into two parts: the first part involved an archival method and the second part used an experiment method. For the archival method, I analyzed 434 firms (2,645 observations) with headquarters in the United States, covering the period between 2010 and 2017, using abnormal accruals, real earnings management, and classification shifting for earnings management, the overall Fortune\'s World\'s Most Admired Companies score for reputation, CEO speeches, and dark personality literature to measure the Dark Tetrad of personality. I ran regressions to test the research hypotheses and found that the Dark Tetrad of personality shows a positive relationship with all types of earnings management. Regarding reputation, only abnormal accruals show a negative relationship with corporate reputation. In turn, the interaction between the Dark Tetrad of personality and corporate reputation is negatively related to all types of earnings management. For the experimental method, I used a 2x2 between-subjects experiment design involving 101 MBA students who, in general, have had experience in management in Brazil and the United States of America. To measure the Dark Tetrad of personality, I used the Short-Dark Triad (Jones & Paulhus, 2014) and the Assessment of Sadistic Personality (Plouffe et al., 2017). For reputation, I adapted the scenarios from Goldberg and Hartwick (1990) and Lafferty (2007). For fraud, I developed two proxies, the first with five situations based on literature addressing accounting issues, and the other based on D\'Souza and Lima (2015). To test the hypotheses, I applied Ordinary Least Squares regressions and Poisson regressions and found that psychopathy, sadism, Machiavellianism, and the Dark Tetrad of personality show a positive relationship with accounting fraud and misrepresentation. Regarding reputation, in all the models, reputation is not related to fraud. On the other hand, in relation to the interaction between the Dark Tetrad of personality and corporate reputation, only highly Machiavellian CEOs are discouraged from committing fraud by a strong reputation. Therefore, this study demonstrated that CEO personality can affect accounting information quality, however, corporate reputation is an intangible resource that influences CEO decision-making, so as a result, reputation helps to increase accounting information quality.